Fazendo o ENADE: concepções e usos da avaliação por coordenadores de cursos de graduação na Universidade Federal do Ceará - Silva, Pablo Rodrigo da (2015)
This dissertation deals with the evaluation of the implementation process of the National Examination of Student Performance (ENADE) at the Federal University of Ceará (UFC), trying to understand the concepts and the uses to which the coordinators of undergraduate courses conceive the practice of institutional evaluation. For this, we carried out a meta-evaluation from the perspective of an in-depth evaluation (LEJANO, 2012; L. C. RODRIGUES, 2008), aiming to: (a) build the historical background of SINAES from its proposals, objectives and purposes to its implementation in the context of UFC and national public policies for higher education, especially the ENADE; (b) analyze the strategies, processes and UFC management’s actions directed to coordination of undergraduate courses in the realization of ENADE; (c) know and understand the uses and meanings attributed by managers selected to the results and processes triggered by the completion of ENADE in the development of undergraduate courses at UFC. It was used in the evaluative research methodology, quantitative and mainly qualitative approach, in conjunction with the theoretical discussion of the concepts institutional evaluation, meta-evaluation and university. We conducted the research through a literature and documentary review, questionnaires and semi-structured interviews. The survey was conducted with coordinators of undergraduate and PROGRAD managers, and applied 42 questionnaires with closed and open questions and interviewed 13 people. The results of evaluative research suggest that ENADE, as public policy of evaluation of higher education institutions, is reframed and experienced at UFC differently to the purposes for which it was originally proposed. The conclusions of the research indicate that the ENADE at UFC is perceived and experienced as institutional assessment from the perspective of monitoring, control and regulation.